2013
DOI: 10.18632/oncotarget.1483
|View full text |Cite
|
Sign up to set email alerts
|

ICRAC controls the rapid androgen response in human primary prostate epithelial cells and is altered in prostate cancer

Abstract: Labelled 5α-dihydrotestosterone (DHT) binding experiments have shown that expression levels of (yet unidentified) membrane androgen receptors (mAR) are elevated in prostate cancer and correlate with a negative prognosis. However, activation of these receptors which mediate a rapid androgen response can counteract several cancer hallmark functions such as unlimited proliferation, enhanced migration, adhesion and invasion and the inability to induce apoptosis. Here, we investigate the downstream signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 51 publications
3
45
4
Order By: Relevance
“…Using mice xenograft models, Dubois and coworkers (25) showed that Orai3 plays a critical role in prostate cancer development in vivo. In stark contrast to this study, Holzmann et al (39) reported a decrease in Orai3 expression in prostate cancer samples compared with normal healthy tissues. Interestingly, these authors also proposed that in prostate cancer cells, Orai1 and Orai3 form heteromultimeric channels, which they referred to as altered calcium release-activated calcium current (I CRAC ) channels (39 (39).…”
Section: Prostate Cancercontrasting
confidence: 99%
See 2 more Smart Citations
“…Using mice xenograft models, Dubois and coworkers (25) showed that Orai3 plays a critical role in prostate cancer development in vivo. In stark contrast to this study, Holzmann et al (39) reported a decrease in Orai3 expression in prostate cancer samples compared with normal healthy tissues. Interestingly, these authors also proposed that in prostate cancer cells, Orai1 and Orai3 form heteromultimeric channels, which they referred to as altered calcium release-activated calcium current (I CRAC ) channels (39 (39).…”
Section: Prostate Cancercontrasting
confidence: 99%
“…In stark contrast to this study, Holzmann et al (39) reported a decrease in Orai3 expression in prostate cancer samples compared with normal healthy tissues. Interestingly, these authors also proposed that in prostate cancer cells, Orai1 and Orai3 form heteromultimeric channels, which they referred to as altered calcium release-activated calcium current (I CRAC ) channels (39 (39). Based on 2-APB pharmacology and molecular knockdown in LNCaP cells, the authors concluded that in normal prostate cells, Orai3 is the major contributor to I CRAC while the decrease in Orai3 expression in prostate cancer cells favors the formation of Orai1-Orai3 heteromultimeric channels (39).…”
Section: Prostate Cancercontrasting
confidence: 99%
See 1 more Smart Citation
“…Modified primer sequences are identical as previously published (Holzmann et al . ): Orai1_1_mod, sense: 5′ OMeC OMeG GCCUGAUCUUUAUCG d(UCU) OMeU OMeT OMeT 3′ Antisense: 3′ OmeG OmeC CGGACUAGAAAUAGCAGA d(A) 5′ Orai1_2_mod, sense: 5′ OMeC OMeA ACAUCGAGGCGGUGA d(GCA) OMeA OMeT OMeT 3′ Antisense: 3′ OMeG OMeT UGUAGCUCCGCCACUCGU d(U) 5′ Negative control siRNA_mod, sense: 5′ OMeA OMeA UUCUCCGAACGUGUC d(ACG) OmeU OmeT OMeT 3′ Antisense: 3′ OmeT OMeT AAGAGGCUUGCACAGUGC d(A) 5′ Control siRNA_mod, sense: 5′ OMeA OMeA AGGUAGUGUAAUCGC d(CUU) OMeG OMeT OMeT 3′ Antisense: 3′ OMeT OMeT UCCAUCACAUUAGCGGAA dC 5′ …”
Section: Methodsmentioning
confidence: 99%
“…Holzmann et al . proposed that ROS-mediated inactivation of ORAI1 may also contribute to higher sensitivity of prostate cancer cells to ROS, due to dampening of SOCE dependent pro-proliferative Ca 2+ signaling [198, 230]. The authors proposed that this altered ORAI1/ORAI3 expression ratio could provide a therapeutic opportunity to target the pro-proliferative actions of SOCE by carefully tuning redox-mediated inactivation to only affect tumor cells [198].…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%